An access scheme based on the random access occasion dynamic allocation - Shaoxiong JING; Yue YUAN; Jiawei XIONG; Junxuan WANG (物联网学报)
With the rapid development of the internet of things (IoT), the application of machine type communication (MTC) in life has grown substantially, and the deployment of machine type devices (MTD) has become more and more intensive.In this case, if there is an unexpected situation such as a power outage and a network failure, a large-scale MTD will initiate access to the base station at the same time when the device is powered on.When the device accesses the base station, it needs to complete the downlink synchronization, system message receiving, random access (RA) and other processes.However, the preamble resources that can be allocated by the base station are limited and cannot meet such a huge access demand, which causes network congestion and affects the access probability and access delay of the device.In order to alleviate the access conflict of RA, a dynamic random access occasion (RO) adjustment scheme was proposed based on the uplink and downlink subframes and physical random access channel (PRACH) configuration, and time-based part of the MTD with high delay requirements allocates specific preamble resources.The simulation results show that this scheme can effectively improve the throughput of the system and reduce the access delay of the device.